Non-infectious granulomatous disorders of the upper lip: clinicopathological analysis of 11 patients - Irene Lafuente-Ibáñez de Mendoza; Emmanuelle Vigarios; Béatrice Herbault-Barres; Javier Alberdi-Navarro; Vincent Sibaud; Delphine Maret; José Manuel Aguirre-Urizar (BMC, 2022)
Abstract Background Non-infectious granulomatous disorders of the upper lip represent a special chapter of oral and maxillofacial pathology. In this work we report a case-series of this process, to analyse its main clinicopathological features and find differential data that allow us improve its diagnosis and understand its pathogenesis. Methods We present 11 cases of non-infectious granulomatous disorders of the upper lip, 8 women and 3 men with an age range of 29-84 years, who have been attended at the Oral Medicine Department of the IUCT (France) and the Oral Medicine Unit of the UPV/EHU (Spain). All clinicopathological data were collected in a specific protocol. Results We recognized 4 different subtypes of non-infectious granulomatous disorders of the upper lip: (1) associated with Crohn's disease (1 case), (2) associated with foreign body (2 cases), (3) associated with gingivitis lichenoid-like (4 cases), (4) idiopathic (4 cases). Conclusions Clinicopathological differences were identified between these subtypes. A good differential diagnosis is necessary in all cases to rule out the presence of local or systemic etiopathogenic factors.